Congenital infection of SARS-CoV-2 in live-born neonates: a population-based descriptive study. (October 2021) - Garcia-Ruiz, Itziar; Sulleiro, Elena; Serrano, Berta; Fernandez-Buhigas, Irene; Rodriguez-Gomez, Leire; Sanchez-Nieves Fernandez, David; Anton-Pagarolas, Andrés; Esperalba-Esquerra, Juliana; Frick, Marie Antoinette; Camba, Fatima; Navarro-Jimenez, Alexandra; Fernandez-Hidalgo, Nuria; et al.
Abstract: Objective: To evaluate the evidence of mother-to-child transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: This is a descriptive, multicentre, observational study in nine tertiary care hospitals throughout Spain. The study population was women with coronavirus disease 2019 during pregnancy. Mother-to-child transmission was defined as positive real-time RT-PCR of SARS-CoV-2 in amniotic fluid, cord blood, placenta or neonatal nasopharyngeal swabs taken immediately after birth. Results: We included 43 women with singleton pregnancies and one with a twin pregnancy, as a result we obtained 45 samples of placenta, amniotic fluid and umbilical cord blood. The median gestational age at diagnosis was 34.7 weeks (range 14–41.3 weeks). The median interval between positive RT-PCR and delivery was 21.5 days (range 0–141 days). Fourteen women (31.8%, 95% CI 18.6%–47.6%) were positive at the time of delivery. There was one singleton pregnancy with SARS-CoV-2 RT-PCR positive in the placenta, amniotic fluid and umbilical cord blood (2.2%, 95% CI 0.1%–11.8%). Nasopharyngeal aspiration was performed on 38 neonates at birth, all of which were negative (0%, 95% CI 0%–9.3%). In 11 neonates the nasopharyngeal aspiration was repeated at 24–48 hours, and one returned positive (9.1%, 95% CI 0.2%–41.3%). Conclusions: The presence of SARS-CoV-2 in placenta, amniotic fluid and cord blood shows that mother-to-child transmission is possible but uncommon.